Qualitative Investigation of Digital Divide in Indonesia: Toward a Comprehensive Framework - Rahman, Arief; Quaddus, Mohammed (ACIS Publisher, 2012)
The issue of digital divide has attracted many researchers for over a decade, yet the understanding of digital divide is not comprehensive. This research examines three commonly recognised orders of the digital divide, which are: economic divide, the inequality of access to ICT associated with economic conditions; access divide, the disparity of access to ICT; and capability divide, the inequality of ability in using ICT, while conceptualising a fourth divide, innovativeness divide, which is defined as the disparity of individual’s willingness to try out any new information technology. The paper presents a tentative model based on extensive literature review which was explored using qualitative method. The findings generate new insights into the relationships among those four orders of digital divide which contribute to the theoretical framework to understand the digital divide more comprehensively and provide evidence on the impact of digital divide on e-government use. Implications for theory and practice are also discussed in this paper.